2011
DOI: 10.3174/ajnr.a2462
|View full text |Cite
|
Sign up to set email alerts
|

Nonbifurcating Cervical Carotid Artery Diagnosed by MR Angiography

Abstract: BACKGROUND AND PURPOSE:A nonbifurcating cervical carotid artery is a branching anomaly in which the ECA has no proximal main trunk. We report its incidence and characteristic features on MRA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
27
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(28 citation statements)
references
References 11 publications
1
27
0
Order By: Relevance
“…The anatomical variation of the present case is considered a variant of the nonbifurcating cervical carotid artery. A non-bifurcating artery may be caused by segmental agenesis of the proximal ICA, causing the major branches of the proximal ECA to develop separately from the terminal segment of the CCA or proximal ICA (8)(9)(10)(11)(12)(13). In the present case, the protrusion was located in the carotid bifurcation at the level of the C4/5 vertebra, where the normal ICA originated.…”
Section: Discussionmentioning
confidence: 99%
“…The anatomical variation of the present case is considered a variant of the nonbifurcating cervical carotid artery. A non-bifurcating artery may be caused by segmental agenesis of the proximal ICA, causing the major branches of the proximal ECA to develop separately from the terminal segment of the CCA or proximal ICA (8)(9)(10)(11)(12)(13). In the present case, the protrusion was located in the carotid bifurcation at the level of the C4/5 vertebra, where the normal ICA originated.…”
Section: Discussionmentioning
confidence: 99%
“…The nonbifurcating cervical carotid artery is a rare disease en- er, appropriate diagnosis is necessary to avoid complications, such as embolic infarctions during interventional radiologic procedures or head and neck surgeries (1,5).…”
Section: Discussionmentioning
confidence: 99%
“…given that the diameter of the non-bifurcating artery is more similar to that of the contralateral ECA as opposed to the ICA. Our review of the literature identified ten case reports [8][9][10][11][12][13][14][15][16][17] and one small retrospective study 18 documenting this vascular anomaly. It is unclear when the first description of a similar anomaly dates back to, but it appears that in 1821, Allan Barns described a case of single carotid vessel without any appreciable bifurcation on cadaveric dissection, and with the vessels that typically arise from the ECA originating from the ICA 19 .…”
Section: Introductionmentioning
confidence: 99%
“…Uchino et al 18 retrospectively reviewed 2866 non-contrast MR angiograms and identified six cases of a non-bifurcating carotid artery, indicating an incidence of 0.21% in a Japanese cohort. The authors state that the incidence of non-bifurcating carotids was more prevalent than previously thought and comparable to the incidence of persistent trigeminal artery, the most common type of carotid anomaly documented to date 20 .…”
Section: Introductionmentioning
confidence: 99%